2021
DOI: 10.6007/ijarbss/v11-i10/11337
|View full text |Cite
|
Sign up to set email alerts
|

Examining Gender Differences on Technology Knowledge and Readiness towards Digitalization of Accounting Profession

Abstract: Digitalization of the work process affects almost all industries due to the Fourth Industrial Revolution. The accounting profession is no exception, urging future accountants to equip themselves with the technological knowledge and readiness to digitize. As the digitalization of the accounting profession is driven by technological advancement, the gender of future accountants may influence the digitalization process. Thus, this is a timely study to examine the gender differences in technology knowledge and tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The findings are in line with previous research, which identified core skills, learning, and innovation skills that require critical thinking and problem-solving abilities, career and life skills that need teamwork, collaboration, and leadership, and digital literacy skills that require skills such as computer literacy and digital fluency necessary for 21st-century learning and work. Therefore, using computers and other digital technologies is essential to develop and apply more important skills to apply learning and prepare the workforce [5]. These results are consistent with previous research, which identified core skills, learning and innovation skills that require critical thinking and problemsolving abilities, career and life skills such as collaboration, teamwork, and leadership, and digital literacy skills that require abilities such as computer literacy and digital fluency as essential skills for 21st-century learning and work.…”
Section: Discussionsupporting
confidence: 88%
“…The findings are in line with previous research, which identified core skills, learning, and innovation skills that require critical thinking and problem-solving abilities, career and life skills that need teamwork, collaboration, and leadership, and digital literacy skills that require skills such as computer literacy and digital fluency necessary for 21st-century learning and work. Therefore, using computers and other digital technologies is essential to develop and apply more important skills to apply learning and prepare the workforce [5]. These results are consistent with previous research, which identified core skills, learning and innovation skills that require critical thinking and problemsolving abilities, career and life skills such as collaboration, teamwork, and leadership, and digital literacy skills that require abilities such as computer literacy and digital fluency as essential skills for 21st-century learning and work.…”
Section: Discussionsupporting
confidence: 88%